Genetic variants in m5C modification core genes are associated with the risk of Chinese pediatric acute lymphoblastic leukemia: A five-center case–control study - Wang, Xueliang; Deng, Decheng; Yan, Yaping; Cai, Mansi; Liu, Xiaodan; Luo, Ailing; Liu, Shanshan; Zhang, Xiaohong; Jiang, Hua; Liu, Xiaoping (Frontiers in Oncology, 2023)
Objective: To explore the effects of the polymorphisms in 5-methylcytosine (m5C) modification core genes on the risk of pediatric acute lymphoid leukemia ALL. Methods: Case-control design and multinomial logistic regression were used to develop models to evaluate the risk of ALL. We intended to investigate the relationship between 5 functional single nucleotide polymorphisms (SNPs) in m5C modification core genes and ALL risk. A total of 808 cases and 1340 controls from South China were genotyped using a TaqMan assay, odds ratios (ORs) and 95% confidence intervals (CIs) were calculated in the logistic regression models to estimate the associations between the selected polymorphisms and pediatric ALL risk. Results: Among the five analyzed SNPs, The NOL1 rs3764909, NSUN4 rs10252 variants conferred a statistically significant increased risk of pediatric ALL, respectively. While NSUN3 rs7653521, NSUN5 rs1880948 and NSUN6 rs3740102 variants were not associated with the risk of ALL. Stratification analyses demonstrated that NOL1 rs3764909 C>A exhibited a significant association with increased pediatric ALL risk in subgroups of common B ALL, pre B ALL, T cell ALL, low and middle risk, other gene fusion types, non-gene fusion, hypodiploid, normal diploid, primitive lymphocytes in marrow <5% on week 12 and MRD<0.01% on week 12 after induced therapy; NSUN4 rs10252 G>A was related to increased risk of ALL children in subgroups of age ≥120 months, normal WBC number, middle risk, non-gene fusion, MRD≥0.01 on day 15-19 and primitive lymphocytes in marrow <5% on day 33 after induced therapy. Compared with the reference haplotype CAGTA, haplotypes CCGTG and ACATA were significantly associated with increased ALL risk. For rs3764909 and rs10252 varieties of alleles were not associated with MRD levels after Chinese Children Cancer Group chemotherapeutics (CCCG) treatment and South China Children Leukemia Group chemotherapeutics (SCCLG) treatment. Conclusions: In conclusion, genetic variants in m5C modification genes were associated with increased pediatric ALL risk and indicated that NOL1 and NSUN4 gene polymorphisms might be a potential biomarker for pediatric ALL.